Respuesta :

to make out table, we will pick random numbers and sub them in for y to find y.

y = -2x - 3....subbing in 0 for x
y = -2(0) - 3
y = -3....so when x = 0, y = -3....(0,-3)

y = -2x - 3...subbing in 1 for x
y = -2(1) - 3
y = -2 - 3
y = -5....so when x = 1, y = -5...(1,-5)

y = -2x - 3...subbing in 2 for x
y = -2(2) - 3
y = -4 - 3
y = -7...and when x = 2, y = -7...(2,-7)

ur table would then be :

   x          y
  0          -3
  1          -5
  2          -7

u can add more points if needed...but I think u can figure it out now.
y=-2x-3

-2(-3)-3= (6)-3= 3
-2(-2)-3=(4)-3= 1
-2(-1)-3=(2)-3= -1
-2(0)-3=(0)-3= -3
-2(1)-3=(-2)-3= -5
-2(2)-3=(-4)-3= -7
-2(3)-3=(-6)-3= -9

x  l   y
-3   3
-2   1
-1   -1
0    -3
1    -5
2    -7
3    -9